Child Mortality Rate for Unintentional Injuries in Mazandaran, Iran During 2010-2018 - Hamed Rouhanizadeh; Mohammad Reza Navaifar; Elham Keyhanian (Mazandaran University of Medical Sciences, 2019)
Background: The deaths of children and adolescents due to accidents in most countries is one of the serious health problems. In Iran, one of the most common causes of death for this age group is unintentional injuries. This study aimed to investigate the child mortality rate for unintentional injuries in Mazandaran, Iran.  Methods: This retrospective cross-sectional study was carried out in Mazandaran province located in northern Iran from October 1, 2010 to March 3, 2018. All deaths due to accidents for children aged 1 month to 18 years were included in the study, and deaths caused by intentional injuries and poisoning were excluded from the study. Results: Of 1,465 deaths, 619 (42.2%) deaths were due to accidents or injuries other than poisoning. Of these, 596 (96.3%) deaths were caused by unintentional injuries. The Mean±SD age of children died by unintentional injuries was 10.46±6.11 years and the frequency of female deaths was 295 cases (49.5%). Among 492 cases of unintentional non-burn injuries, the reasons for death were: traffic accidents (71.7%), drowning (16%), falling (4.4%), non-traffic-related head trauma (3.6%), asphyxia (1.6%), limbs injury (0.6%), bullet shot (0.4%), explosion (0.4%), visceral injury (0.4%) and unclassified causes (0.6%). Conclusions: A significant percentage of deaths among children and adolescents occurred due to unintentional injuries. Vehicle accident was the most common cause of death followed by drowning and falling. Mortality rate in summer was reported to be higher than in other seasons.